A comparative analysis of biopharmaceutics classification system and biopharmaceutics drug disposition classification system: A cross‐sectional survey with 500 bioequivalence studies1. Issue 9 (11th April 2013) - Cristofoletti, Rodrigo; Chiann, Chang; Dressman, Jennifer B.; Storpirtis, Silvia; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract Although policies of waiving bioequivalence studies are part of the legal framework of various regulatory agencies, there is no harmonization with regard to extension of the biowaiver to drugs other than those with high solubility and high permeability, nor is there any consensus or official endorsement of the biopharmaceutics drug disposition classification system (BDDCS). To better understand the applicability of the biowaiver, we carried out a cross‐sectional survey to estimate the relative risk of obtaining nonbioequivalent (non‐BE) or bioinequivalent (BIE) results for drug products containing drugs belonging to each of the biopharmaceutics classification system (BCS) and BDDCS classes. Five hundred bioequivalence studies were randomly sampled from a database of the Brazilian Health Surveillance Agency (ANVISA). The drugs were classified according to the BCS and BDDCS, to evaluate how characteristics related to drug and dosage form influence the outcome of bioequivalence studies. The relative risk of obtaining a non‐BE result was approximately four times lower for drugs in classes 1 and 3 of BCS or BDDCS when compared with class 2 drugs. Thus, it seems that the final outcome of a bioequivalence study is strongly influenced by the solubility of the drug, but not by its intestinal permeability or extent of metabolism. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3136–3144, 2013